Penguatan Demokrasi dari Desa di Masa Pandemi Covid-19: Problematika Pengembangan Program Desa Anti Politik Uang - Purwaningsih, Titin; Pahlevi, Moch Edward Trias; Amrurobbi, Azka Abdi; Khatami, Muhammad Iqbal; Nuryanti, Sri (Jurnal Politik Profetik, 2023)
Village can become an arena for strengthening democracy because national and regional and even village political agendas all lead to the village political arena. However, democracy in villages is also often haunted by the practice of money politics. Responding to the phenomenon of money politics in society and effort to strengthen democracy at the village level, Bawaslu of the Republic of Indonesia is implementing the Anti-Money Politics (APU) Village program as a preemptive and preventive measure. This research aims to examine further efforts to strengthen village democracy during the pandemic by identifying and evaluating the APU Village Program in Indonesia. This research also uses qualitative methods with data collection techniques, namely interviews, focus group discussions, and expert meetings. This research undertook in four provinces—West Java, Central Java, South Sulawesi, and North Kalimantan—were the sites of the research. According to the study’s findings, Bawaslu lacks a vision, a roadmap, a specific budget, indications for towns deserving of becoming APU towns, and collaboration in the planning of APU Villages. From an institutional standpoint, Bawaslu is now lacking in a framework, a thorough assessment, local actors, and instructional materials. Bawaslu has not developed human resources, conducted extensive training, evaluated the comprehension of village actors, or established an APU Village volunteer team in the area of human resources.